REVISION DE LOS GENEROS DIPLODISCUS DIESING 1836 Y MEGALODISCUS CHANDLER 1923 TREMATODA PARAMPHISTOMOIDEA - HOLLIS BRAVO, MARGARITA (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1942)
A cheap, simple, and convenient stain for blood is described which supplies all the staining details obtained by a pan optic stain Methylene blue is used first, followed by Giemsa
ANS INST BIOL
Keywords: REVISION, GENEROS, DIPLODISCUS, DIESING, TREMATODA, PARAMPHISTOMOIDEA; CIENCIAS MEDICAS; PATOLOGIA; PARASITOLOGIA